2019
DOI: 10.1186/s43088-019-0012-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of Anthocleista vogelii in serum antioxidant defence system in cadmium-induced oxidative stress in Wistar rats

Abstract: Background: Cadmium (Cd) toxicity, which runs across the food chain, is chiefly regulated by in vivo antioxidant defence system or through antioxidant supplementation of biological systems predisposed to this environmental stressor. The present study was designed to examine the role of Anthocleista vogelii leaves in Cd-induced oxidative stress in the serum of Wistar rats through the application of response surface methodology (RSM) and biomonitoring of selective responses: malondialdehyde (MDA), catalase (CAT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
4
2
0
Order By: Relevance
“…The significant increase in lipid peroxidation and glutathione peroxidase (GPx) in Cd-challenged rats compared to control and significant decrease in glutathione (GSH), superoxide dismutase (SOD) and catalase (CAT) in both the liver and kidey, recorded in this study is a clear indication of the Cd-induced oxidative stress. This finding agrees with the confirmed ability of Cd to induce oxidative stress in the rat tissues (Mona et al, 2018, Orororo et al, 2018bApiamu et al, 2019;Jacopo et al, 2020;Innih et al, 2021;Renuka et al, 2021;Poli et al, 2022). Cd, unlike other heavy metals is unable to generate free radicals by itself, however, according to Galan et al (2001), it can generate hydroxyl radical, superoxide radical, and nitric oxide radicals indirectly.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The significant increase in lipid peroxidation and glutathione peroxidase (GPx) in Cd-challenged rats compared to control and significant decrease in glutathione (GSH), superoxide dismutase (SOD) and catalase (CAT) in both the liver and kidey, recorded in this study is a clear indication of the Cd-induced oxidative stress. This finding agrees with the confirmed ability of Cd to induce oxidative stress in the rat tissues (Mona et al, 2018, Orororo et al, 2018bApiamu et al, 2019;Jacopo et al, 2020;Innih et al, 2021;Renuka et al, 2021;Poli et al, 2022). Cd, unlike other heavy metals is unable to generate free radicals by itself, however, according to Galan et al (2001), it can generate hydroxyl radical, superoxide radical, and nitric oxide radicals indirectly.…”
Section: Resultssupporting
confidence: 84%
“…Due to the fact that Cd possesses extremely low tolerable exposure limit and a lengthy natural half-life, it bio-accumulates in humans and animal where it brings about severe damage to the liver, kidneys and other organs, tissues and cells mainly through the induction of oxidative stress (Goyer, 1997;Jacopo et al, 2020). It has been reported that Cd drains glutathione (an endogenous antioxidant molecule), restrain electron transport process in the mitochondrial, dislodge Zinc and other redox-active metals, and incapacitate antioxidant enzymes which results in enhanced production of reactive oxygen species (ROS) (Mona et al, 2018, Orororo et al, 2018Geng et al, 2019;Apiamu et al, 2019;Innih et al, 2021;Poli et al, 2022). Current research in Cd toxicity focuses on finding antioxidants that can treat Cd intoxication in biological systems, with emphasis on the antioxidant potentials of various plant extracts, which contain carotenoids, flavonoids, and other polyphenols that play pivotal roles in antioxidant defense mechanisms against Cd-induced oxidative injury (Orororo et al, 2018a;Genchi et al, 2022).…”
mentioning
confidence: 99%
“…The quadratic models for the prediction of NKA activity in all tissues showed a lack of fit with comparable critical F and p values, and this suggested significant goodness of fit for the experimental data. Again, the perfect linearity between predicted and experimental (actual) values can be corroborated with earlier reports, stating that the difference of less than 0.2 between predicted and adjusted R 2 values hereby validated the observed linearity in the diagnostics plots for gill, hepatic and renal NKA activity [48,[51][52][53]. This further corroborates the feasibility of the respective models for the prediction of NKA activity under the influence of Pb and Zn toxic actions respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Also, the 3D response surface plots explained the nature of the interaction between two process variables at a fixed level of the third process variable and their concerted effects on NKA activity in the tissues of exposed C. gariepinus. In studies, the concerted effect of the variables on response was dependent on their nature of the interaction, which was considered significant by rising contour bridges or elliptical mounds, but insignificant interactions between variables were associated with straight contour lines [48,56]. This study hereby corroborates the inhibitory response of NKA activity in tissues of exposed C. gariepinus to Zn and Pb co-exposure in a time-dependent manner.…”
Section: Discussionsupporting
confidence: 76%
“…32,33 CAT, an antioxidant enzyme known to catalyze the decomposition of H2O2 into metabolic water (H2O) and molecular oxygen under the influence of Zn cofactor. 25,27,34 In this empirical survey, exposure to Pb toxicity and co-treatment with different exogenous antioxidant types (AA and BHT) shows the trending mosaic of CAT activity in various tissues of Wistar rats (Figure 3). In group II rats treated with a single dose of Pb by intraperitoneal injection, significant reductions (p < 0.05) in serum, hepatic and renal CAT activities were observed when compared with group I rats.…”
Section: Resultsmentioning
confidence: 83%